2013
DOI: 10.1021/ef401528k
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Char Direct Chemical Looping Gasification Using NiO-Modified Iron Ore as an Oxygen Carrier

Abstract: Chemical looping gasification (CLG) is considered as a novel gasification technology because gas-phase oxygen of the gasifying medium can be replaced by lattice oxygen of the oxygen carrier. The gasifying mediums (e.g., pure O 2 and steam) used as the oxygen source can apparently improve the char conversion in traditionally biomass gasification. Similarly, the objective of this study is to investigate char CLG with the oxygen carrier as an individual oxygen source. A NiO-modified iron ore oxygen carrier was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…A similar gasification concept allowing for decent fuel conversions, without requiring an ASU is the chemical looping gasification (CLG) process, where biomass gasification is also carried out in two separate reactors (see Figure 1) [15,[19][20][21][22]. Just as the related chemical looping combustion (CLC) process, CLG is realized using two coupled fluidized bed reactors, in order to attain good heat and mass transport characteristics [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A similar gasification concept allowing for decent fuel conversions, without requiring an ASU is the chemical looping gasification (CLG) process, where biomass gasification is also carried out in two separate reactors (see Figure 1) [15,[19][20][21][22]. Just as the related chemical looping combustion (CLC) process, CLG is realized using two coupled fluidized bed reactors, in order to attain good heat and mass transport characteristics [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The first works at laboratory scale appeared in 2013, and the efforts for the development of this technology have been increasing since then, particularly in China. There are laboratory-scale works, mainly based on thermogravimetric data or batch fluidized beds, analysing the use of different oxygen carriers based on nickel [255,256] copper oxide [224,257,258], iron oxide (both natural iron ore, synthetic and waste materials) [259][260][261][262][263][264][265][266][267][268], copperiron [269,270] and nickel-iron [271,272]. The different forms of biomass used in those studies vary from woody biomass, pine sawdust and rice straw to biomass char and microalgae.…”
Section: Syngas/h 2 Production By the Chemical Looping Gasification Pmentioning
confidence: 99%
“…Intensive references demonstrated that the presence of a spinel structure improved the reduction kinetics and enhanced the reducibility of Fe 2 O 3 . 14,[41][42][43][44] In the reduced samples, the unmodied iron ore was mainly reduced into FeO and Fe 3 O 4 ; the CuO-iron ore was reduced into Cu, FeO and Fe; the NiO-iron ore was reduced into Ni, FeO, (Ni, Fe) and Fe; while the CeO 2 -iron ore was reduced into FeO, CeFeO 3 and Fe. The reduction of Fe 2 O 3 to Fe 3 O 4 did not contribute to the production of hydrogen in the oxidation step.…”
Section: Cyclic Testsmentioning
confidence: 99%